Woody angiosperm diversity and indigenous conservation in Ghimbo Pomuan Sacred Forest, Kampar, Riau Province, Indonesia - HIKMAH HIDAYAH; FRIDA KUNTI SETIOWATI; FAJAR ADINUGRAHA; SITI ZUBAIDAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hidayah H, Setiowati FK, Adinugraha F, Zubaidah S. 2025. Woody angiosperm diversity and indigenous conservation in Ghimbo Pomuan Sacred Forest, Kampar, Riau Province, Indonesia. Biodiversitas 26: 6240-6251. Woody angiosperms are the dominant component of tropical forest biodiversity, with important ecological, cultural, and economic roles. However, their conservation remains challenging, particularly in sacred forests managed under customary systems that are underdocumented in scientific literature. The Ghimbo Pomuan Sacred Forest in Kampar, Riau Province, Indonesia, offers an opportunity to explore the biocultural relationships between people and woody plant species. This study aimed to document woody angiosperm diversity in the Ghimbo Pomuan Sacred Forest and examine indigenous conservation practices at the forest level. Field exploration combined vegetation sampling in 35 plots (20 x 20 m) and semi-structured interviews with indigenous elders. We recorded 30 woody angiosperm species from 18 families, with Myrtaceae and Dipterocarpaceae being the most dominant. Species diversity was moderate (H′ = 2.637-2.915), with 24 genera and several species holding global conservation concern, such as Rubroshorea uliginosa (Endangered), Rubroshorea balangeran (Vulnerable), and Madhuca ovata (Critically Endangered). Indigenous management practices include customary prohibitions, collective governance (sekepomuan), and sanctions for violating these rules. Particular species, such as Syzygium spp. and Gluta renghas, were protected for both ecological and spiritual reasons, supporting natural regeneration and forest succession. This study underscores the importance of incorporating indigenous knowledge into conservation policies and reaffirms the significance of sacred forests as vital refuges for biodiversity.